A note on observations on cetaceans in the western Indian sector of the Southern Ocean (20-56°S and 45-57°30’E), January to March 2004 - Jayaksankar, P.; Krishnan, Anoop A.; Rajagopalan, M.; Krishnakumar, P. K. (J. Cetacean Res. Manage., 2023)
A multi-disciplinary and multi-institutional pilot expedition was organised by the National Centre for Antarctic and Ocean Research (NCAOR) to the ice-free areas of the Western Indian Ocean sector of the Southern Ocean onboard ORV Sagar Kanya during the austral summer of 2004 (January-March). This survey, conducted by the Central Marine Fisheries Research Institute (CMFRI), is the first Indian attempt to survey for cetacean diversity in the Southern Ocean. The ultimate objective is to determine distribution, relative abundance, migration patterns and critical habitat parameters. 68% of a total of 13 sightings (22 individuals) were positively identified and species observed included Antarctic minke whales (Balaenoptera bonaerensis), fin whales (B. physalus), sei whales (B. borealis) and blue whales (B. musculus). The blue whales were not identified to the sub-species level. The highest concentration of cetaceans was between 35° and 37°S (along 45°E) and between 48° and 53°S (along 45°E). Relatively small numbers of cetaceans were observed during the present cruise, possibly because most of the cetacean sighting effort was made during inclement sea conditions. Results on the sighting characteristics and occurrence patterns of the cetaceans in relation to the region and hydrographical parameters are discussed briefly vis a vis published information from the Southern Ocean.